Diagnostic accuracy of Magnetic Resonance Imaging using liver tissue specific contrast agents and contrast enhanced Multi Detector Computed Tomography: A systematic review of diagnostic test in Hepatocellular Carcinoma (HCC). Issue 4 (November 2018) - Usman, S.; Smith, L.; Brown, N.; Major, V.
Abstract: Objectives: The aim of this systematic review is to investigate diagnostic accuracy of Magnetic Resonance Imaging (MRI) scans using liver specific tissue contrast media over contrast enhanced Multi Detector CT (MDCT) in diagnoses of Hepatocellular Carcinoma (HCC) in patients with chronic liver disease. Key findings: A total of 8 diagnostic studies were identified and generally considered of high quality. The studies reported sufficient evidence on sensitivity and specificity, which was synthesised and summarised providing an overview of the evidence. Findings indicate that MRI scans using liver specific tissue contrast have a better diagnostic performance compared to contrast enhanced MDCT in diagnostic work-up of HCC in patients with chronic liver disease. Conclusion: The current review identified sufficient high quality studies reporting statistical difference (P < 0.05), to establish the superiority of gadoxetetic acid enhanced MRI for sensitivity and specificity in comparison to MDCT in the diagnosis of HCC in chronic liver disease. Highlights: Hepatocellular Carcinoma is the most common global primary liver cancer in persons with chronic liver disease. Gadoxetetic acid enhanced MRI is more sensitive in diagnosing HCC compared to contrast enhanced MDCT. There is no difference in specificity between gadoxetetic acid enhanced MRI and contrast enhanced MDCT. Combination of 3T MRI and gadoxetetic acid (Gd-EOBDTPA) has further improved diagnostic accuracy of HCC.